MANAJEMEN KONFLIK DALAM PENMANAJEMEN KONFLIK DALAM PENDIDIKAN ISLAM MULTIKULTURAL: INTEGRASI PENDEKATAN MODERN DAN NILAI-NILAI ISLAM DIDIKAN ISLAM MULTIKULTURAL: INTEGRASI PENDEKATAN MODERN DAN NILAI-NILAI ISLAM - Dedi Hendriyanto; H. Naswin; M. Zakaria; Ansori Ansori; Iwan Aprianto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The cultural, ethnic, linguistic, and religious diversity within multicultural Islamic educational institutions has the potential to generate conflicts that may affect the effectiveness of educational management. However, conflict should not merely be viewed as a negative phenomenon but also as an opportunity for organizational learning and improvement when managed appropriately. This article aims to analyze the concept of conflict management in multicultural Islamic education, identify the forms and sources of conflict, examine conflict management strategies through the integration of modern management approaches and Islamic values, and explain the role of leadership in fostering an inclusive, harmonious, and sustainable educational environment. This study employed a qualitative approach using a Systematic Literature Review (SLR) based on library research. Relevant literature was selected according to predetermined inclusion criteria and analyzed using content analysis techniques. The findings indicate that conflicts in multicultural Islamic education primarily arise from differences in values, culture, communication, interests, organizational structure, and religious understanding. Effective conflict management requires the integration of modern management strategies with Islamic values, including shura (consultation), tabayyun (verification), tasamuh (tolerance), ishlah (reconciliation), and 'adl (justice), supported by inclusive leadership and multicultural education. The study concludes that the synergy between multicultural education, Islamic values, and inclusive leadership forms a comprehensive conceptual framework for conflict management that promotes a culture of peace and enhances the quality of Islamic educational institutions. ABSTRAK Keberagaman budaya, etnis, bahasa, dan pemahaman keagamaan dalam lembaga pendidikan Islam multikultural berpotensi memunculkan konflik yang memengaruhi efektivitas penyelenggaraan pendidikan. Konflik tidak selalu bersifat negatif, tetapi dapat menjadi sarana pembelajaran organisasi apabila dikelola secara tepat. Artikel ini bertujuan menganalisis konsep manajemen konflik dalam pendidikan Islam multikultural, mengidentifikasi bentuk dan sumber konflik, mengkaji strategi pengelolaan konflik melalui integrasi pendekatan manajemen modern dengan nilai-nilai Islam, serta menjelaskan peran kepemimpinan dalam menciptakan lingkungan pendidikan yang inklusif, harmonis, dan berkelanjutan. Penelitian menggunakan pendekatan kualitatif dengan metode Systematic Literature Review (SLR) melalui studi kepustakaan. Literatur yang relevan diseleksi berdasarkan kriteria inklusi dan dianalisis menggunakan teknik content analysis. Hasil penelitian menunjukkan bahwa konflik dalam pendidikan Islam multikultural terutama dipengaruhi oleh perbedaan nilai, budaya, komunikasi, kepentingan, struktur organisasi, dan pemahaman keagamaan. Pengelolaan konflik yang efektif memerlukan integrasi strategi manajemen modern dengan nilai-nilai Islam, seperti syura, tabayyun, tasamuh, ishlah, dan 'adl, yang diperkuat melalui kepemimpinan inklusif serta pendidikan multikultural. Penelitian ini menyimpulkan bahwa sinergi antara pendidikan multikultural, nilai-nilai Islam, dan kepemimpinan inklusif membentuk kerangka konseptual yang komprehensif dalam manajemen konflik sehingga mampu mendukung terciptanya budaya damai dan meningkatkan kualitas penyelenggaraan pendidikan Islam.